Theoretical and Practical Aspects of Using Anatomically Detailed Puppets while Interrogating Extremely Vulnerable Persons (Law and Safety, 2020)
The article is focused on one of the urgent tasks for domestic scholars and practitioners – the development and implementation of non-traumatic methods of interrogation. Thus, the author of the article defines theoretical and practical aspects of using anatomically detailed puppets during the interrogation of extremely vulnerable persons – minor victims and witnesses of rape, sexual abuse, corruption of minors, human trafficking, pornography, etc., including children with physical or (and) mental disorders.The tactics of interrogation of these extremely vulnerable persons need to be improved through the introduction of the “Green Room” method declared by international and national standards, one of the elements of which is a set of anatomically detailed puppets. It has been noted that despite mentioning about the method of interrogation in the domestic normative, scientific and methodological literature, there are no detailed studies of the rules and conditions of using “Green Room” and the possibility of applying anatomical puppets.Theoretical approaches and practical aspects of modern world experience of interrogating extremely vulnerable persons with the use of anatomically detailed puppets have been analyzed. It has been also determined that puppets are used as an anatomical model, demonstration aid, memory stimulation, diagnostic tool or “icebreaker” in the world theory and practice of interviewing children.The author has determined the tasks of applying of the set of anatomically detailed puppets: 1) actualization of recollection; 2) visual demonstration by the child of the mechanism of criminal actions committed against the child; 3) increasing the reliability and significance of information about the circumstances of the commission; 4) prevention of secondary traumatization of minor victims and eyewitnesses of certain types of crimes.The author has formulated the rules and has determined conditions for using anatomically detailed puppets during the interrogation of extremely vulnerable persons. The tactics of interrogation of minor victims and witnesses of certain types of crimes have been improved. The emphasis has been placed on the need for widespread introduction of this non-traumatic method of interrogation of minors into the training of future police officers, advanced training or (and) specialization of existing police officers, and into the investigative and judicial practice.
Keywords: extremely vulnerable persons; rules and conditions of using anatomically detailed puppets; interrogation of minor victims and witnesses